Size optimisation of silver nanoparticles synthesised by gallic acid using the response surface methodology - Ahani, Mina; Khatibzadeh, Marziyeh (Micro & nano letters, 2020)
This work reports the synthesis of silver nanoparticles (AgNPs) from Ag nitrate (AgNO3) using the gallic acid (GA) as a green methodology without utilisation of hazardous chemicals. The effects of variables such as AgNO3 concentration, GA concentration, and pH on the average particle size of AgPs were optimised through response surface methodology based on the central composite design at three levels to obtain the desired response, i.e. minimum average particle size. The formation of AgNPs at each experiment was characterised by ultraviolet–visible (UV–vis) spectroscopy and the average particle size was measured by dynamic light scattering (DLS). To evaluate the significance of factors on the response and their quantitative effects, analysis of variance was carried out. The results indicated that the pH was the most effective factor on the response. The AgNPs synthesised at optimised conditions (5.42 mM of AgNO3, 6.25 mM of GA, and pH = 9.02) were characterised by X-ray diffraction, DLS, field-emission scanning electron microscope, energy dispersive X-ray, transmission electron microscopy, UV–vis spectroscopy, and Fourier-transform infrared spectroscopy. On the basis of the DLS, the average particle size of AgNPs obtained 8 nm, which was in satisfactory agreement with the predicted value (7.51 nm) by model.